Influence of surfactants on the properties of electrodeposited nickel composite coatings reinforced with mechanically alloyed CoCrMoNiW high entropy alloy - Venkatesh, Koduru; Karthik, V. (Surface & coatings technology, 2025)
In the present study, the CoCrMoNiW high entropy alloy (HEA) particles reinforced nickel composite coatings are fabricated through the electrodeposition route. The dispersion and non-agglomeration of hard reinforcement particles in the electrolytic bath play a vital role in the electrodeposition of composite coatings. Hence, the influences of surfactant types i.e., anionic (sodium dodecyl sulphate, SDS), cationic (cetyltrimethylammonium bromide, CTAB), and non-ionic (polyethylene glycol, PEG), on the characteristics and properties of Ni-HEA composite coatings have been studied. The CoCrMoNiW HEA particles are fabricated through mechanical alloying of elemental powders. The x-ray diffraction analysis reveals mixed phase consisting of BCC phase with minor quantity of FCC phase in the mechanically alloyed HEA particles. The coating prepared with SDS surfactant achieved the highest thickness, approximately 140 μm. The critical load of 57 N in the scratch test, Vickers hardness number of 721 VHN, coefficient of friction of 0.28, and specific wear rate of 1.9 × 10−7 mg/N-m were obtained for the composite coatings fabricated using SDS surfactant, these represent the highest performance values among all the fabricated coatings. The corrosion resistance is also high for the composite coating obtained using SDS surfactant (0.13 mpy) compared to the other coatings. The superior properties of the composite coating produced with SDS surfactant can be attributed to the higher zeta potential of the HEA particles, which promotes better dispersion in the electrolyte, which contributes to the uniform and stable dispersion of HEA particles without agglomeration, leading to the homogeneous distribution of HEA particles in the electrodeposited composite coating. •CoCrMoNiW HEA reinforced Ni coatings by electrodeposition for the first time.•Influence of anionic, cationic, and neutral surfactants on coating properties studied.•Sodium dodecyl sulphate surfactant works well owing to its higher zeta potential.•Ni-HEAp-SDS composite coating has 3.5 times higher hardness than ED-Ni coating.•Ni-HEAp-SDS coating has highest corrosion and wear resistance.